Snow White with the red hair. 9 - Akiduki, Sorata (Shojo beat manga., 2020)
"Shirayuki is an herbalist famous for her naturally bright-red hair, and the prince of Tanbarun wants her all to himself! The prince from the neighboring kingdom, Zen, rescues her from her plight, and thus begins their love story ... Shortly after Shirayuki and Ryu's arrival in Lilias, a mysterious ailment breaks out. Now the two herbalists find themselves in a race against time to find a cure for the illness before it spreads throughout the city. And what will Zen and friends so when they catch word of this outbreak on their way to Wirant?"--Provided by publisher